2015
DOI: 10.1111/ecc.12346
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of triple-negative breast cancer: a comparison between younger (<60) and elderly (≥60) patients

Abstract: Triple-negative breast cancer (TNBC) has attracted more attention both clinically and experimentally because of its high-risk biological characteristics and lacking of effective treatment method. The tumour characteristics, patterns of recurrence and metastasis, therapy methods and prognosis in younger TNBC patients have been widely formulated, but the relevant data of the elderly people are lacking. We conducted this retrospective study to compare and analyse the above-related characteristics between the youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
4
15
1
Order By: Relevance
“…These associations with tumor characteristics underscore that basal-like tumors tend to have more aggressive characteristics, while luminal A tumors tend to be more indolent. These associations have been relatively consistent across studies and in different racially defined subpopulations [ 25 27 ].…”
Section: Discussionmentioning
confidence: 71%
“…These associations with tumor characteristics underscore that basal-like tumors tend to have more aggressive characteristics, while luminal A tumors tend to be more indolent. These associations have been relatively consistent across studies and in different racially defined subpopulations [ 25 27 ].…”
Section: Discussionmentioning
confidence: 71%
“…Other investigators have reported equivalent survival among elderly TNBC patients compared to younger patients despite the reduced rate of treatment with chemotherapy in this age group. [16][17][18] Konigsberg et al observed elderly patients had significantly fewer local, bone and secondary lymph node metastases than younger patients with TNBC. 19 Better survival in older TNBC patients with comparatively less treatment may be related to a less aggressive nature of TNBC in older patients with a decreased likelihood of distant metastases and presentation at lower stage than younger patients.…”
Section: Me Th Odsmentioning
confidence: 99%
“…Their findings should be transferrable to many other countries and health systems (O'Donovan et al 2015). Chau et al (2015) and Qiu et al (2015) both conducted traditional clinical trials comparing younger and older patients. The latter study looks at differences in clinicopathological features and prognosis of triple-negative breast cancer (TNBC) between younger (<60 years old) and elderly (≥60 years old) patients.…”
mentioning
confidence: 99%
“…The retrospective nature of their study and the definition of TNBC is a limitation of the study, and there is definitely a need for more research (funding) in this area in the future so that prospective trials are possible in older patients (Qiu et al . ). Chau et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation